2016
DOI: 10.1016/j.cbd.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced changes in gene expression from anterior and posterior gills of Callinectes sapidus (Crustacea: Portunidae) with implications for crustacean ecological genomics

Abstract: Decapods represent one of the most ecologically diverse taxonomic groups within crustaceans, making them ideal to study physiological processes like osmoregulation. However, prior studies have failed to consider the entire transcriptomic response of the gill – the primary organ responsible for ion transport – to changing salinity. Moreover, the molecular genetic differences between non-osmoregulatory and osmoregulatory gill types, as well as the hormonal basis of osmoregulation, remain underexplored. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…Interestingly, the expression of the Na + /K + ATPase (NKA) remained unchanged in crab gills at all salinities tested in the present study, while it has been shown to play important roles in ion uptake of crustaceans and fishes, usually with increased expression under low salinity 11 , 16 , 29 , 33 , 40 . As NKA expression could vary with time 12 , 41 , a thorough study on its expression with more time points would help to elucidate its role in osmoregulation of the mud crabs. Nevertheless, we have identified a suite of ion transport genes involved in osmoregulation of crabs, similar to other decapods in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the expression of the Na + /K + ATPase (NKA) remained unchanged in crab gills at all salinities tested in the present study, while it has been shown to play important roles in ion uptake of crustaceans and fishes, usually with increased expression under low salinity 11 , 16 , 29 , 33 , 40 . As NKA expression could vary with time 12 , 41 , a thorough study on its expression with more time points would help to elucidate its role in osmoregulation of the mud crabs. Nevertheless, we have identified a suite of ion transport genes involved in osmoregulation of crabs, similar to other decapods in general.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a number of studies on salinity adaptation of euryhaline crabs have been conducted, showing the involvement of ion transport, amino acid metabolism, and energy metabolism in the process 12 17 . However, these studies have two main limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity changes can directly affect the activity of enzymes regulating osmotic pressure and gene expression. Therefore, studies on the effects of salinity on fish have mainly focussed on osmoregulatory organs (gill, intestine and kidney) (Havird et al 2016 ; Zhang et al 2016 ). Although the liver is not an osmoregulatory organ, it is the major source of energy for osmoregulatory organs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, transcriptomic analysis of fish in response to salinity stress has mainly focused on genes and enzymes related to osmotic organs and osmotic pressure regulation (Havird et al 2016 ), and studies on liver metabolism have not yet been reported. The effects of low salinity stress on gene expression in the liver of E. moara were investigated for the first time in this study using the Illumina digital gene expression system.…”
Section: Discussionmentioning
confidence: 99%
“…1). A large number of relatively recent independent studies have started to generate publically deposited large transcriptomic data sets from food crop species and other related malacostracan species providing ample raw data for our study (Christie et al, 2014; Ghaffari et al, 2014; Sun et al, 2015; Li et al 2015; Meyer et al 2015; Stahl et al, 2015; Verbruggen et al 2015; Truebano et al 2016; Kim et al 2016; Havird et al 2016; Tan et al, 2016; and complete set of references in supplementary table 1).…”
Section: Introductionmentioning
confidence: 99%